Habits of Mind: A Study in Anticipating Learning Loss at State Universities in Riau Province - Indra Primahardani; M. Yogi Riyantama Isjoni; Filma Aliya Sari (Institut Agama Islam Ma'arif NU (IAIMNU) Metro Lampung, 2023)
Habits of mind a lecturer's is very important so that students can overcome obstacles in learning activities. For approximately two years the implementation of learning is carried out online, so this condition has a negative impact on students and students. One of these impacts is the occurrence of Learning Loss in students. In general, the research that has been carried out has identified research data through the instrument developed by Costa and Kallik which consists of many question indicators. However, the indicators developed by Marzano have not been widely used. These indicators include: Self Regulation, Critical Thinking and Creative Thinking. This research focuses on the Habits of Mind Lecturers of Social Studies Education Department at State Universities in Riau Province in Anticipating Learning Loss. The research conducted is descriptive quantitative research. To analyze the index and the sustainability status of the Habits of Mind Lecturer skills, a Multidimensional Scaling (MDS) analysis approach was used with the help of the RapHoM software (modified Rapfish). The habits of mind skills of lecturers at state universities in Riau Province are classified as quite sustainable. His condition is certainly a warning that the habits of mid skill of a lecturer are needed in order to increase student interest, motivation and achievement through lecturer habits in transmitting positive thinking habits to students. Keywords: Anticipating Learning Loss, Habits of Mind, Creative Thinking